Abbau der kalten Progression seit 2016 – eine Zwischenbilanz; Curbing the fiscal drag: A provisional assessment - Matthias Warneke (Wirtschaftsdienst, 2021)
Seit 2016 findet ein Abbau der kalten Progression statt. Der Autor zeigt beispielhaft, inwiefern die Steuerzahler:innen durch diese Reform in den vergangenen fünf Jahren entlastet wurden und wertet dies als Zwischenerfolg für den Bund der Steuerzahler. Dieser Fortschritt sollte jedoch durch weitere Reformen abgesichert werden. – – It took decades of political discussion for lawmakers to begin adjusting the income tax tariff for inflation in order to curb the fiscal drag. Since 2016, the fiscal drag has been reduced by almost exteuro 32 billion according to our estimates. That is certainly a substantial amount given the low inflation rates in the period 2016-2021. We illustrate these effects graphically and also numerically for individual taxpayers. We find that further reforms are needed. A specific formula should be integrated into the Income Tax Act so that the tariff is adjusted automatically to inflation. In the long run, average income growth rates should be used for indexation instead of inflation rates.
Keywords: H20; H24; 330